Artikel Review : Agen Pengendali Hayati Serangga Hama Penggerek Buah Kopi (Hypothenemus hampei Ferr.) pada Tanaman Kopi - Wahyudi, Christosie Immanuel (Universitas Cokroaminoto Palopo, 2025)
Coffee is an important commodity for the Indonesian economy, which is the third largest coffee producer in the world after Brazil and Vietnam. Coffee cultivation in Indonesia began in 1699. Coffee has become a widely known agricultural product and is expected to increase state revenues from exports. The types of coffee cultivated include Robusta, Arabica, and Liberica, with Robusta dominating production. Indonesia. Coffee farmers face problems in the form of decreased quality and quantity of production caused by pest attacks. One of the main pests is the coffee berry borer (CBO), known by the scientific name Hypothenemus hampei. This pest is difficult to control and can damage coffee fruit and beans, lowering its market price. The distribution of CBO is almost evenly distributed throughout Indonesia, with varying levels of damage in various regions, such as 64% in Lampung and 80% in Papua. This pest has a complete life cycle with four stages: eggs, larvae, pupae, and adults. Females can produce 50 eggs, which hatch in 5-9 days. The CBO life cycle takes about 25 days, with varying lifespans for females and males. PBKo attacks occur on coffee berries aged 8 weeks until harvest, which can damage coffee beans and reduce yields. The age of the coffee plant also affects the quantity of fruit produced and the distribution of pests. Coffee plants that are not exposed to direct sunlight have higher temperatures and humidity, supporting the growth of PBKo. PBKo pest control can be done biologically/biological control. Some PBKo pest control agents include predators, parasitoids, entomopagenic fungi, entomopagenic bacteria, and entomopagenic nematodes.